2012
DOI: 10.3892/etm.2012.463
|View full text |Cite
|
Sign up to set email alerts
|

Transcervical intrauterine levobupivacaine infusion or paracervical block for pain control during endometrial biopsy

Abstract: The aim of this study was to determine pain during endometrial biopsy by comparing the use of intrauterine instillation of levobupivacaine or paracervical block with a placebo in a randomized, double-masked trial in premenopausal and postmenopausal women. A total of 90 women were enrolled in the study. Patients were allocated to either the control or case groups. Group 1 consisted of 30 cases with intrauterine anesthesia with 5 ml 0.5% levobupivacaine. Group 2 consisted of 30 patients who underwent paracervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…Although several studies concluded that Pipelle significantly produced less pain than D&C [10,11,12], other studies reported the occurrence of mild-to-severe pain during Pippelle endometrial sampling [13,14,15]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies concluded that Pipelle significantly produced less pain than D&C [10,11,12], other studies reported the occurrence of mild-to-severe pain during Pippelle endometrial sampling [13,14,15]. …”
Section: Discussionmentioning
confidence: 99%
“…This might be related to the use of cervical tenaculum in some women during Pipelle endometrial sampling as its contribution for pain occurrence cannot be denied. However, other risk factors for associated pain in the Pipelle procedure might have a role such as negative pressure induced by the procedure or during intrauterine Pipelle insertion [11,12,13]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traction of the cervix with the tenaculum, insertion of a Pipelle through the cervix and the biopsy itself are all potential causes of pain [11]. Medications blocking or reducing the nerve impulses during any part of the procedure may result in pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Pipelle procedure is more comfortable than dilation and curettage, patients may still suffer from discomfort and pain. Several pain-reduction methods have been evaluated in the literature; for example, intrauterine anesthesia, intrauterine anesthesia plus a nonsteroidal anti-inflammatory drug (NSAID), topical analgesia, intrauterine anesthesia plus buccal misoprostol, and transcutaneous electrical nerve stimulation have been tested [5,6,7,8,9,10,11]. The local benzocaine study was the only study that did not demonstrate pain reduction [7].…”
Section: Introductionmentioning
confidence: 99%